Contribution of Additional Glutamic Acid and Fructose in The Formation of Flavor Compounds in Green Tea - Khaeruddin Aris; Andriati Ningrum; Supriyadi Supriyadi (Indonesian Food and Nutrition Progress, 2023)
Green tea in Indonesia has an astringent and bitter taste due to its high catechin content. Adding amino acids and reducing sugars in green tea processing will increase the desirable flavor and cover the astringent and bitter flavors by increasing the Maillard reaction. Research on the manufacture of green tea with the addition of glutamate and fructose in fresh tea leaves has never been explored. This study aims to find a combination of glutamic acid (0%, 0.35%, 0.7%, 1.05%, 1.4%) and fructose (0%, 0.13%, 0.26%, 0.39%, 0.52%) to improve the flavor profile in green tea. The samples were evaluated for their antioxidant activity, amino acid, volatile, sensory evaluation, and color analysis. The results showed that adding glutamate and fructose increased the antioxidant activity of amino acid compounds and decreased the catechin content in green tea. Thus, the best treatment obtained was glutamate (1.05%) and fructose (0.26%), which increased the Maillard reaction in the formation of flavor compounds in green tea.